2019
DOI: 10.1111/bcp.13969
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous flucloxacillin treatment is associated with a high incidence of hypokalaemia

Abstract: Intravenous flucloxacillin is one of the most frequently used high-dose penicillin therapies in hospitalized patients, forming the cornerstone treatment of invasive Staphylococcus aureus infection. Being a nonreabsorbable anion, flucloxacillin has been suggested to cause hypokalaemia, although the frequency and magnitude of this unwanted effect is unknown. In a retrospective cohort, we investigated the incidence and extent of hypokalaemia after initiation of intravenous flucloxacillin or ceftriaxone therapy. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
1
5
1
Order By: Relevance
“…The incidence of hypokalaemia in our study was lower compared to the cohort study from Van der Heijden et al (23.7% vs 42%) 5 . As flucloxacillin‐induced hypokalaemia is considered to develop dose‐dependently, this difference is likely explained by the inclusion of patients with high‐dose flucloxacillin only (≥6 g/24 h) in the study by Van der Heijden et al 5 This assumption is confirmed by the incidence of 50% in the subgroup with high‐dose flucloxacillin (>8 g/24 h) in our study.…”
Section: Discussioncontrasting
confidence: 86%
See 3 more Smart Citations
“…The incidence of hypokalaemia in our study was lower compared to the cohort study from Van der Heijden et al (23.7% vs 42%) 5 . As flucloxacillin‐induced hypokalaemia is considered to develop dose‐dependently, this difference is likely explained by the inclusion of patients with high‐dose flucloxacillin only (≥6 g/24 h) in the study by Van der Heijden et al 5 This assumption is confirmed by the incidence of 50% in the subgroup with high‐dose flucloxacillin (>8 g/24 h) in our study.…”
Section: Discussioncontrasting
confidence: 86%
“…We found that the incidence of hypokalaemia was 23.7%. As this is notably higher than previous reports (approximately 13.5%), our study confirms that intravenous flucloxacillin treatment is associated with an increased risk of developing hypokalaemia 1,5 . The incidence of hypokalaemia in our study was lower compared to the cohort study from Van der Heijden et al (23.7% vs 42%) 5 .…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Methylmalonate acts as nonreabsorbable anions, enhancing potassium excretion by increasing transtubular potential difference. Such non-reabsorbable anion effect has long been well described with penicillins, also acting as non-reabsorbable anion [ 34 , 35 ]. Indeed, we found a positive correlation between urinary potassium and urinary methylmalonate as well as a negative correlation between serum potassium and urinary methylmalonate.…”
Section: Discussionmentioning
confidence: 99%